INVESTIGATION OF HEAVY METALS AND PESTICIDES DISTRIBUTION AS A POLLUTION CONTROL IN CIRATA RESERVOIR, WEST JAVA - Azzuri Yalfis, Lavia
Water pollution that occurs in the Citarum river comes from human activities such as industry, agriculture, and domestic resulting in a decrease in water quality. This situation has a impact on the Cirata Reservoir that blocks and receives streams from the Citarum river. In addition, activities that occur in reservoirs such as cage cultures (KJA) also have an impact on water quality in the Cirata reservoir. This study aims to analyze heavy metals and pesticides found in the Cirata reservoir due to pollution by the activities of the inside and outside of the reservoir. Sampling activities are carried out by taking samples of water at several points in the Cirata reservoir in a composite to be able to represent the water quality of the reservoir. Laboratory tests were carried out at the Integrated Laboratory in Balingtan, Pati and the Balingtan Agrochemical Materials Residue Laboratory, Bogor. The results of the laboratory test that found a heavy metals Pb, Cd, Cr, Co, Cu, Zn, and Ni, organochlorine and organophosphate pesticides in the Cirata reservoir. The data are then analyzed by the Inverse Distance Weighted (IDW) interpolation method for the spatial distribution maps using power values ratio 1.2 and 3. The IDW analysis results show that several types of heavy metals such as Pb and Cd have even distribution at all sampling points in the reservoir, indicating that the pollutant source that produces the metal is still polluting the Cirata reservoir to date and the nature of heavy metals that are difficult to decompose. For the distribution of organochlorine and organophosphate pesticides found in small concentrations because they are easily degraded and do not exceed the quality standards set by the Government Regulation of the Republic of Indonesia No. 82 of 2001 and West Java Regional Regulation No. 39 of 2000. Calculation of the Pollution Index (PI) also done on the water sample. Heavy metals in the Cirata Reservoir waters are included in the category of lightly polluted with a PI value <5, organochlorine pesticides are categorized as lightly polluted with the results of PI value <5 and organophosphate pesticides categorized as good with the PI value <1. The results show that the pollution that occurs in the Cirata reservoir can be caused by the activities of the inside and outside of the reservoir which reduce water quality, so that good environmental management needs to be done as pollution control.